New layered uranium phosphate fluorides: syntheses, structures, characterizations, and ion-exchange properties of A(UO2)F(HPO4).xH2O (A = Cs+, Rb+, K+; x = 0-1). - Ok, K; Baek, J; Halasyamani, P; O'Hare, D (2006)
Single crystals of three new layered uranium phosphate fluorides, A(UO2)F(HPO4).xH2O (A = Cs+, Rb+, and K+; x = 0-1) have been synthesized by hydrothermal reactions using UO3, H3PO4, HF, and corresponding alkali metal halides as reagents. Although all three new materials have layered structures, each of them contains different structural motifs within the layer. While Cs(UO2)F(HPO4).0.5H2O and Rb(UO2)F(HPO4) reveal noncentrosymmetric crystal structures, K(UO2)F(HPO4).H2O crystallizes in a centrosymmetric space group. In addition, the ion-exchanged phases for all three materials are highly crystalline. Crystal data: Cs(UO2)F(HPO4).0.5H2O, orthorhombic, space group Pca21 (No. 29), with a = 25.656(5) A, b = 6.0394(12) A, c = 9.2072(18) A, and Z = 4; Rb(UO2)F(HPO4), orthorhombic, space group Cmc21 (No. 36), with a = 17.719(4) A, b = 6.8771(14) A, c = 12.139(2) A, and Z = 8; K(UO2)F(HPO4).H2O, monoclinic, P21/n (No. 14), with a = 6.7885(14) A, b = 8.7024(17) A, c = 12.020(2) A, beta = 94.09(3), and Z = 4.